Evaluation of Pangkep District Archery Athletes on Pre-Porprov Achievements - Hasyim Hasyim; Irfan Irfan; Nurliani Nurliani (STKIP Muhammadiyah Kuningan, 2022)
Pangkep archery athletes have competed in Pre Porprov to go to Porprov Sinjai in 2022; based on the results of an evaluation that has been carried out by researchers, that mentality which includes an athlete's anxiety, is very important to note because it has a significant impact on the athlete's achievement, things that must also be considered in addition to Athlete anxiety is an athlete's physical condition itself because the combination of the suitable mental and reasonable physical is an achievement. In archery, the physical component that supports is the strength of the arm muscles because the arm is the main foundation for aiming at a target. The research method used in this research is descriptive analysis and also correlation and regression tests. Based on the results of a study that has been carried out that there is a significant relationship between anxiety and arm muscle strength (58%) and shows that the anxiety level of Pangkep archery athletes is in the moderate category, as many as 13 athletes (43.3%) and arm muscle strength is in the middle class. Twenty-seven athletes (90%). The conclusion is that the anxiety level of Pangkep archery athletes is in the medium category, and the arm muscle strength of Pangkep, archery athletes, is in the moderate type, which affects the performance of Pangkep archery athletes to compete in Porporv Sinjai in 2022.